(untitled) (Bioscience Journal, 2019)
The aimed of this study was to evaluate the effects of different dosages of turkey litter on soil’s chemical attributes and yield of the Urochloa decumbens in classified as degraded pasture. The work was performed at the municipality of Mineiros-GO between October/2011 and September/2013 in Quartzipsamment soil. The treatments consisted in applications of 0, 3, 6, 9 and 12 Mg ha-1 of turkey litter at a randomized-complete blocks design with four replications. Was evaluated the fodder’s productivity and the following soil’s chemical attributes: organic matter, hydrogenionic potential (CaCl2), phosphorus (resin), potassium, calcium, magnesium, cation exchange capacity and base saturation of soil. In general terms, the increase of turkey litter’s doses increased the grass productivity and the supply of nutrients of the soil, maintaining the balance of the soil-plant system. The dosage of 12 Mg ha-1 year-1 of turkey litter ensure higher amounts in the soil’s chemical attributes and in the productivity of dry mass of Urochloa decumbens.